Analysis of Changes in Heat Exchanger Performance in PK-XXX Aircraft with Material Modification Using Ansys Program - Angga A, Antonius; Ruhiyat, Nanang (Budapest International Research and Critics University, 2021)
Airplanes are popular transportation for the community in general because they have various advantages over other existing transportation. Airplanes have a relatively short time to travel between islands. Safety and comfort are major factors in the operation of an aircraft. One of the safety factors in an aircraft is the air supply, one of the supporting components of the air supply is a heat exchanger. The heat exchanger keeps the temperature of the air entering the Air Cycle Machine at its operating temperature. The Heat Exchanger in this journal is a type for the Boeing 737-500 aircraft which has a significant decrease in performance which results in damage to ACM components. A plate and frame heat exchanger with aluminum alloy material will be compared with a copper heat exchanger using the Ansys program to determine the effectiveness of both. The analysis will be carried out using the calculation method as well as running tests on the Heat Exchanger, and using Ansys for testing material modification.